2021
DOI: 10.1016/j.ebiom.2021.103544
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spike N501Y mutation on neutralizing activity and RBD binding of SARS-CoV-2 convalescent serum

Abstract: Background Several SARS-CoV-2 lineages with spike receptor binding domain (RBD) N501Y mutation have spread globally. We evaluated the impact of N501Y on neutralizing activity of COVID-19 convalescent sera and on anti-RBD IgG assays. Methods The susceptibility to neutralization by COVID-19 patients’ convalescent sera from Hong Kong were compared between two SARS-CoV-2 isolates (B117-1/B117-2) from the α variant with N501Y and 4 non-N501Y isolates. The effect of N501Y on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Studies have shown that there are many hydrophobic amino acids on the site of antigen and antibody binding ( 12 ), so we also took the sites that are mutated into hydrophobic amino acids in the S protein as the research objects of interest. We hypothesized that epitopes generated based on these mutated sites as well as the mutated sites in the most immunogenic region of the S protein named RBD ( 13 ) might be more likely to be presented to the cell surface by MHC molecules and recognized by T cells. In addition, the high-frequency D614G mutation that appeared in these five variants was also considered to be interesting, since several studies emphasized the impact of D614G variant on transmission effectiveness ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that there are many hydrophobic amino acids on the site of antigen and antibody binding ( 12 ), so we also took the sites that are mutated into hydrophobic amino acids in the S protein as the research objects of interest. We hypothesized that epitopes generated based on these mutated sites as well as the mutated sites in the most immunogenic region of the S protein named RBD ( 13 ) might be more likely to be presented to the cell surface by MHC molecules and recognized by T cells. In addition, the high-frequency D614G mutation that appeared in these five variants was also considered to be interesting, since several studies emphasized the impact of D614G variant on transmission effectiveness ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that N501Y may induce neutralization resistance in the serum from convalescent COVID-19 patients 49 or the N501Y mutant may alter the availability of epitopes that are targeted by the antibodies. Moreover, resistance could be enhanced with the combination of E484K/K417N mutations 50 - 52 . The results are consistent to our data using monoclonal and polyclonal antibodies and the serum from convalescent patients and vaccinees (Figure 4 and 5 ), suggesting that N501Y/E484K/K417N mutations improve the inhibition of S-ACE2 interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although further studies involving more clinical strains and serum samples, especially using a panel of viruses within the same lineage to determine the impact of virus variants on neutralization as performed by Lu et al [15] , are essential to obtain a firm conclusion, this study assessed neutralizing antibody titers using authentic SARS-CoV-2 variants. A majority of the studies in the literature employ pseudo-virus-mediated systems [16] , [17] because of the difficulty in handling SARS-CoV-2 with regards to the regulations and infectivity.…”
Section: Discussionmentioning
confidence: 99%